VD_FINDINFO Jug / 2023 / 116 vom 25. August 2022 - VD Tribunal cantonal (2022)
DIFFAMATION, DÉFAUTCONTUMACE, RETRAITVOIE DE DROIT, FRAIS DE LA PROCÉDURE, PROTECTION DE LA PERSONNALITÉ | 28 CC, 173 CP, 407 al. 1 let. a CPP (CH), 426 al. 2 CPP (CH)